Comparative Studies of Methods for Accurate Hurst Parameter Estimation - Kulikovs, M.; Sharkovsky, S.; Petersons, E. (Elektronika ir Elektrotechnika, 2010)
Over the last decade the traffic of the packet-based networks shows self-similar or long-range dependent nature. Such behaviour raises issues of accuracy in resource allocation and related guarantee required of QoS parameters for data flow. One of the popular mechanisms for QoS parameters guaranty is Measurement-based Admission Control (MBAC). In it’s turn, the efficiency of the MBAC mechanism is tightly related to the accuracy of traffic parameters estimation. The appropriate buffer size estimation is one of primary tasks in MBAC for QoS parameters guarantee. Hurst parameter which describes the level of self-similarity is used for this purpose. The accuracy of it’s estimation is important as otherwise underutilization or over-saturation of the system may occur that would cause high packet losses. The present paper provides a thorough overview of currently known methods for Hurst parameter estimation and presents research results of accuracy levels of each of them.